Enhanced P2P Services Providing Multimedia Content. (1st November 2007) - Ardizzone, E.; Gatani, L.; La Cascia, M.; Lo Re, G.; Ortolani, M.
Abstract : The retrieval facilities of most Peer-to-Peer (P2P) systems are limited to queries based on unique identifiers or small sets of keywords. Unfortunately, this approach is very inadequate and inefficient when a huge amount of multimedia resources is shared. To address this major limitation, we propose an original image and video sharing system, in which a user is able to interactively search interesting resources by means of content-based image and video retrieval techniques. In order to limit the network traffic load, maximizing the usefulness of each peer contacted in the query process, we also propose the adoption of an adaptive overlay routing algorithm, exploiting compact representations of the multimedia resources shared by each peer. Experimental results confirm the validity of the proposed approach, that is capable of dynamically adapting the network topology to peer interests, on the basis of query interactions among users.